Black Phosphorus Nanosheets for Mild Hyperthermia-Enhanced Chemotherapy and Chemo-Photothermal Combination Therapy - Wang, Sheng (Nanotheranostics, 2017)
Near-infrared (NIR) light triggered photothermally enhanced cellular internalization strategy shows great potential to improve antitumor effect to fight against cancer. In this work, a black phosphorus (BP) nanosheet-based nanomedicine, which is composed of BP nanosheet, human serum albumin (HSA) and paclitaxel (PTX), was developed for mild hyperthermia-enhanced intracellular drug delivery and chemo-photothermal combination therapy. BP nanosheet was successfully synthesized by a one-pot biomimetic synthesis method using HSA as exfoliating agent and capping agent. Meanwhile, PTX can be efficiently loaded by HSA via hydrophobic interactions. The PTX-loaded HSA functionalized BP (BP-HSA-PTX) exhibits great photothermal performance, excellent biodegradability/biocompatibility, and effective drug loading. Upon NIR laser illumination, mild hyperthermia (~43 °C) or photothermal effect can be achieved to improve the intracellular drug delivery efficiency and antitumor effect of BP-HSA-PTX. Our results indicate that HSA-functionalized BP has great potential for the loading, delivery, cellular uptake enhancement of chemotherapeutics and chemo-photothermal combination antitumor effect.